Future of Artificial Intelligence in Manufacturing– A Literature Review - Aarushi S. Gode; Asawari Pimpalkar; Dr. Rajeshkumar Sambhe (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Artificial Intelligence (AI) is emerging as an influential tool in contemporary manufacturing, enabling industries to work more effectively and efficiently. This article delves into how AI, Machine Learning (ML), and Deep Learning (DL) are employed in several processes of manufacturing, ranging from quality checks and predictive maintenance to robotics and production planning. The technologies contribute towards minimizing errors, reducing downtime, and enhancing the quality of the product. Above all, they help human workers by taking on repetitive and dangerous tasks and allowing for more valuable human-machine interaction. The research identifies instances where AI enhances decision-making and flexibility in rapidly changing market conditions. It also deals with high setup costs, unavailability of skilled workers, and data management problems. Despite these challenges, AI holds immense potential to create safer, more sustainable, and more responsive factory floors. This review seeks to provide students, engineers, and decision-makers with a clear perspective on how AI can transform the future of manufacturing in a friendly manner.
Keywords: Artificial Intelligence; Machine Learning; Manufacturing; Automation; Robot; Challenges; Technology